2013
DOI: 10.1002/jemt.22210
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and immunohistochemical study of early repair of alveolar sockets after the extraction of molars from alendronate‐treated rats

Abstract: The aim of the present research was to analyze ultrastructural and immunohistochemical aspects of the alveolar repair after the extraction of molars of alendronate (ALN)-treated rats. Wistar rats received 2.5mg/kg body wt/day of ALN during 14 days previously and 7, 14 and 21 days after the extraction of the second mandibular molar. Specimens were fixed in 2% glutaraldehyde + 2.5% formaldehyde under microwave irradiation, decalcified in 4.13% EDTA and paraffin embedded for TRAP histochemistry and immunohistoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 47 publications
0
19
0
2
Order By: Relevance
“…Most studies that aimed to interfere in alveolar bone resorption by osteoclasts employ bisphosphonates with higher anti‐resorptive potency like zoledronic acid (Aguirre et al, ). However, in the present study the ALN was employed because it is the most prescribed antiresorptive drug for the prevention and treatment of bone diseases (Russell, ) and usually comprises long‐term administration regimens, which represents a risk of developing osteonecrosis when associated to oral surgeries or pathologies like periodontal disease (Aghaloo et al, ; Yamamoto‐Silva et al, ). In the present study, a high dose of ALN proven to impair the bone resorption by osteoclasts (Bradaschia‐Correa et al, ) was daily administered to rats, starting seven days before the induction of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies that aimed to interfere in alveolar bone resorption by osteoclasts employ bisphosphonates with higher anti‐resorptive potency like zoledronic acid (Aguirre et al, ). However, in the present study the ALN was employed because it is the most prescribed antiresorptive drug for the prevention and treatment of bone diseases (Russell, ) and usually comprises long‐term administration regimens, which represents a risk of developing osteonecrosis when associated to oral surgeries or pathologies like periodontal disease (Aghaloo et al, ; Yamamoto‐Silva et al, ). In the present study, a high dose of ALN proven to impair the bone resorption by osteoclasts (Bradaschia‐Correa et al, ) was daily administered to rats, starting seven days before the induction of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Soundia et al reported that ZA and OPG‐Fc monotherapy significantly compromised bone healing of extracted healthy teeth with periradicular disease, whereas osseous healing of tooth extraction sockets was almost normal . On the other hand, Kim et al reported that ZA/Dex combination therapy and ZA monotherapy significantly increased glucose metabolism at the extraction site at 4 weeks after tooth extractionusing F‐fluorodeoxy glucose PET/CT, in accordance with the significant prevalence of BRONJ‐like lesions (Table ) …”
Section: Resultsmentioning
confidence: 68%
“…Zoledronic acid (ZA) and osteoprotegerin (OPG)‐Fc monotherapy were used to create BRONJ‐ and DRONJ‐like lesions in five studies, respectively, whereas ZA was administered in combination with chemotherapeutic agents and/or dexamethasone (DEX) to develop BRONJ‐like lesions in four studies . Alendronate monotherapy was also used to create BRONJ‐like lesions in one study . On the other hand, an anti‐angiogenesis agent‐related ONJ model has not been developed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations